N6-methyladenosine RNA modification regulates strawberry fruit ripening in an ABA-dependent manner - Zhou, Leilei; Tang, Renkun; Li, Xiaojing; Tian, Shiping; Li, Bingbing; Qin, Guozheng (Genome Biology, 2021)
Background Epigenetic mark such as DNA methylation plays pivotal roles in regulating ripening of both climacteric and non-climacteric fruits. However, it remains unclear whether mRNA m6A methylation, which has been shown to regulate ripening of the tomato, a typical climacteric fruit, is functionally conserved for ripening control among different types of fruits. Results Here we show that m6A methylation displays a dramatic change at ripening onset of strawberry, a classical non-climacteric fruit. The m6A modification in coding sequence (CDS) regions appears to be ripening-specific and tends to stabilize the mRNAs, whereas m6A around the stop codons and within the 3′ untranslated regions is generally negatively correlated with the abundance of associated mRNAs. We identified thousands of transcripts with m6A hypermethylation in the CDS regions, including those of NCED5, ABAR, and AREB1 in the abscisic acid (ABA) biosynthesis and signaling pathway. We demonstrate that the methyltransferases MTA and MTB are indispensable for normal ripening of strawberry fruit, and MTA-mediated m6A modification promotes mRNA stability of NCED5 and AREB1, while facilitating translation of ABAR. Conclusion Our findings uncover that m6A methylation regulates ripening of the non-climacteric strawberry fruit by targeting the ABA pathway, which is distinct from that in the climacteric tomato fruit.